Proceedings of 10th World Construction Symposium 2022 2022
DOI: 10.31705/wcs.2022.11
|View full text |Cite
|
Sign up to set email alerts
|

Application of computer vision for construction progress monitoring

Abstract: Progress monitoring of construction work is crucial to identify the discrepancies between the as-built product and as-planned design and take necessary action based on the results. Construction work is time consuming and labour intensive. However, the use of new technologies, such as computer vision (CV), in construction progress monitoring (CPM) can minimise human errors. Thus, the aim of this study was to explore the current applications of CV in the construction industry in general and in the different stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The results of this work are consistent with the research findings of [1][2][3][4], who stated that BIM technology and the REVIT software tool could minimize much of human errors and achieve a higher degree of precision. Also, these results are consistent with the findings of [5][6][7], who reported that the REVIT program could save considerable effort and time that would be significantly consumed by engineers to estimate the construction project cost. Also, the results of this study are compatible with [8][9][10], who analyzed the critical role of the BIM technology and REVIT software in estimating project costs and found that using the REVIT program can significantly cut effort, time, and cost required to calculate the construction projects costs that have higher complexity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this work are consistent with the research findings of [1][2][3][4], who stated that BIM technology and the REVIT software tool could minimize much of human errors and achieve a higher degree of precision. Also, these results are consistent with the findings of [5][6][7], who reported that the REVIT program could save considerable effort and time that would be significantly consumed by engineers to estimate the construction project cost. Also, the results of this study are compatible with [8][9][10], who analyzed the critical role of the BIM technology and REVIT software in estimating project costs and found that using the REVIT program can significantly cut effort, time, and cost required to calculate the construction projects costs that have higher complexity.…”
Section: Discussionsupporting
confidence: 90%
“…The construction projects' activities and parameters associated with each building task have been growing in the last decades, leading to higher challenges and difficulties for quantity surveyors to calculate the cost of each project as the complexity of these projects is remarkable. Additionally, if the calculation process relies on human efforts, the cost assessment will contribute to various errors and less precision, and it will consume much time [5][6][7]. In this context, designers, planners, and scholars have been working through decades of Research and Development (R&D) to develop BIM technology and REVIT software package that can be capable of providing state-of-the-art cost-evaluation techniques by which these problems can be alleviated and resolved.…”
Section: Introductionmentioning
confidence: 99%